S-equol Partially Restored Endothelial Nitric Oxide Production in Isoflavone-deficient Ovariectomized Rats. Issue 5 (May 2015) - Ohkura, Yoshinori; Obayashi, Satoshi; Yamada, Kazuki; Yamada, Mikiko; Kubota, Toshiro
Abstract : Background: S -equol is known as an estrogenic substance, but its ability to restore vascular endothelial function is unknown. The aim of this study was to investigate the impact of S -equol on endothelial function and intimal thickening under isoflavone- and estrogen-deficient circumstances. Methods: Twelve-week-old female Sprague–Dawley rats were bilaterally ovariectomized and assigned to one of the 3 groups: control, isoflavone-deficient (ID), or ID plus equol (n = 12, respectively). The control group received a normal diet containing isoflavones, while ID and ID plus equol groups received isoflavones-free diet. At 16th week, subcutaneous administration of S -equol (200 μg/d) started in the ID plus equol group. At 18th week, endothelial denudation of the left common carotid artery was performed in all groups, and thoracic and carotid arteries were collected at 20th week. Results: In thoracic artery, endothelium-dependent relaxation, cyclic guanosine monophosphate levels in the tissue, and endothelial nitric oxide (NO) synthase expression and phosphorylation were significantly higher in the groups of ID plus equol and control than in the ID. The ratio of intima to media of the injured carotid artery in the control group was the lowest. Conclusions: Removal of dietary soy isoflavones decreased endothelium-derived NO level in ovariectomized rats. S -equol supplementation partially improved NO-related endothelial function.